Genetic basis analysis of key Loci in 23 Yannong series wheat cultivars/lines - Xiao, Luning; Jin, Yuli; Liu, Wei; Liu, Jie; Song, Huajie; Li, Dong; Zheng, Jianpeng; Wang, Dongmei; Yin, Yan; Liu, Yang; Wang, Hao; Li, Linzhi; et al. (Frontiers in Plant Science, 2022)
Fungal diseases, drought, pre-harvest sprouting (PHS) and other biotic and abiotic stresses have seriously affected the quality and yield in wheat production. Identifying related genes/loci in released cultivars/lines can provide reference information and theoretical basis for wheat improvement. Yannong series wheat cultivars/lines have distinctive characteristics in wheat cultivars and play an important role in genetic improvement and production of Chinese wheat production system. To dissect their genetic basis of the stress-resistant traits, in this study, 23 representative Yannong series wheat cultivars/lines were tested by 58 molecular markers for 40 genes related to adaptability, disease resistance and stress tolerance to clarify the genetic composition of the key loci. The results showed that most of the tested wheat accessions carried dwarfing genes RhtB1b/RhtD1b/Rht8 and recessive vernalization genes vrn-A1/vrn-B1/vrn-D1/vrn-B3. It was also consistent with the phenotypic traits of tested Yannong series wheat which were dwarf and winter or semi winter wheat. In addition, the overall level of seedling powdery mildew resistance in 23 Yannong wheat cultivars/lines was moderate or inadequate. Eleven accessions carried none of the tested Pm genes and twelve accessions carried Pm2, Pm6, Pm42 and Pm52 singly or in combination. Then, 23 wheat cultivars/lines were also tested by 17 diagnostic markers for 14 Yr genes. The results showed that 16 wheat cultivars/lines were likely to carry one or more of tested Yr genes, whereas Yannong 15, Yannong 17, Yannong 23, Yannong 24, Yannong 377, Yannong 572 and Yannong 999 carried none of the tested Yr genes. Moreover, in our study, nine markers for four genes related to drought tolerance and PHS were used to evaluate the stress tolerance of the 23 wheat cultivars/lines. The results indicated that all 23 wheat cultivars/lines carried drought resistance genes Ta-Dreb1/TaCRT-D, indicating that they had the drought resistance to the extent. Except for Yannong 30, Yannong 377, Yannong 390, Yannong 745 and Yannong 1766, other wheat cultivars/lines carried one to three elite PHS-resistant alleles Vp-1Bc/Vp-1Bf/TaAFP-1Bb.